2012
DOI: 10.1155/2012/379738
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for the Development of Rapid Serological Assays for Surveillance and Diagnosis of Infections Caused by Zoonotic Flaviviruses of the Japanese Encephalitis Virus Serocomplex

Abstract: Flaviviruses are responsible for a number of important mosquito-borne diseases of man and animals globally. The short vireamic period in infected hosts means that serological assays are often the diagnostic method of choice. This paper will focus on the traditional methods to diagnose flaviviral infections as well as describing the modern rapid platforms and approaches for diagnostic antigen preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 170 publications
(192 reference statements)
0
24
0
Order By: Relevance
“…This test is a highly valuable tool because IgM antibodies are hard to detect using VNTs or HITs [133,135] and exhibit less cross-reactivity than IgG antibodies [136,137]. …”
Section: Serological Cross-reactions Between West Nile and Relatedmentioning
confidence: 99%
“…This test is a highly valuable tool because IgM antibodies are hard to detect using VNTs or HITs [133,135] and exhibit less cross-reactivity than IgG antibodies [136,137]. …”
Section: Serological Cross-reactions Between West Nile and Relatedmentioning
confidence: 99%
“…The symptoms of infection in humans ranged from a simple febrile headache to meningoencephalitis, and the severity of the symptoms increases with the patient age (1)(2)(3)(4)(5). Cross-reactivity in diagnostic assays between SLEV and other flaviviruses complicates differential diagnosis (6). This is particularly challenging in Argentina where there are dengue virus (DENV) outbreaks frequently, history of jungle yellow fever, and Zika virus (ZIKV) activity was demonstrated and YFV vaccination is common in some regions (7)(8)(9)(10) Regarding the specific antiviral response pattern against SLEV, IgM antibodies persistence has been detected in some patients showing that the presence of IgM might not be indicative of acute infection (11,12).…”
Section: Manuscriptmentioning
confidence: 99%
“…This alteration contributes for the formation and activation of E protein homodimers. Researchers suggested that the extremely conserved N glycosylation motif N 15 -X 16 -T 17 in JEV PrM and its N-glycan substituents are essential for several stages of JEV biology: PrM biogenesis, virus release and pathogenesis. The E protein is the largest structural protein, comprising of approximately 500 aminoacids, with up to two potential glycosylation sites.…”
Section: Viral Replication and Morphogenesismentioning
confidence: 99%